A beryllium-zirconium alloy and its application in nuclear fusion
By developing beryllium zirconium alloy, adjusting its composition and process conditions, forming specific phase composition and grain structure, the problem of irradiation and swelling of existing beryllium neutron proliferators in high temperature environments is solved, and the neutron proliferation performance is improved and Toughness achieves the effects of high temperature, high toughness and high neutron proliferation rate.
Patent Information
- Application Number
- CN202211648859.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-21
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-12-21
AI Technical Summary
The existing beryllium neutron proliferators have obvious irradiation swelling under high temperature and high irradiation environments, which may endanger the operation of the nuclear fusion reactor. The neutron proliferation performance of beryllium decreases after adding Ti, and its toughness is not good.
Develop a beryllium zirconium alloy with a composition of Bea(ZrbMc)Xd. By adjusting the alloy composition and process conditions, the phase composition and fine grains are controlled, and the face-centered cubic structure phase and close-row hexagonal structure are equal, which increases its high temperature. High toughness and neutron proliferation performance.
The high temperature and high toughness and high neutron proliferation rate of beryllium zirconium alloy are achieved, with a melting point greater than 1800℃, a neutron proliferation rate of nearly 1, and has excellent irradiation swelling and mechanical properties, which are suitable for the neutron proliferation field and high temperature environment.
Smart Images

Figure CN116121613B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal materials, and in particular relates to a beryllium-zirconium alloy and its application in nuclear fusion. Background Art
[0002] With China joining the International Thermonuclear Experimental Reactor (ITER) project, nuclear fusion energy, as an internationally recognized clean energy, is gradually coming into people's view. However, the realization of commercial controlled nuclear fusion still faces three major bottlenecks, one of which is the self-sustaining problem of fusion tritium fuel. Neutron breeders and neutron breeder materials are one of the keys to solving this bottleneck problem.
[0003] Beryllium is an excellent neutron breeding material. The binding energy of beryllium neutrons in the nucleus is small (1.666MeV), equivalent to 1 / 5 to 1 / 6 of the energy of most stable atoms. Neutrons are easily released through high-energy particle bombardment, including (n,2n) reactions, thereby achieving neutron multiplication. Metallic beryllium has no obvious irradiation swelling (<3%) below 400°C and transmutation He injection below 3000appm, and has been selected as the neutron breeder in the blanket of the ITER nuclear fusion reactor. However, the future commercial controlled fusion reactor (DEMO) environment is more harsh, with higher operating temperatures (600-900°C), larger irradiation doses, and helium injections as high as 20,000appm. The irradiation swelling of beryllium is particularly obvious (>3%), which may endanger the operation of the reactor.
[0004] Beryllium intermetallic compounds, such as Be 12 Ti has attracted the attention of researchers, and foreign countries, especially Japan, have paid attention to Be 12 Ti has been extensively studied. However, due to the addition of Ti, Be 12 The neutron multiplication performance of Ti is greatly reduced, and its toughness is very poor, which is extremely unfavorable for the production and use of alloys and neutron breeder pellets. Therefore, the research of new alloys with higher toughness and higher neutron multiplication performance is of great significance in the field of fusion neutron multiplication and even in the high temperature field. Summary of the invention
[0005] In order to overcome the above problems existing in the prior art, the present invention provides a beryllium-zirconium alloy and its application in nuclear fusion, which are used to solve the above problems existing in the prior art.
[0006] A beryllium-zirconium alloy, wherein the atomic percentage expression of the beryllium-zirconium alloy material composition is Be a (Zr b M c )X d, where M is one or more of Y, Ti, V, Mn, Fe, Mg, Cr, Co, W, Mo, Nb, Pb, Bi, Ta, Hf, Tl, Re, X is one or more of O, C, N, P, S, Si, Al, Ca, Sc, Ni, Cu, U, 65 ≤ a ≤ 97, 3 ≤ b ≤ 35, 0 ≤ c ≤ 35, 0 < d ≤ 3, and a + b + c + d = 100.
[0007] For the aspects and any possible implementation manners described above, a further implementation manner is provided. When 0 < d ≤ 2, 0 ≤ c ≤ 3.57, c < b ≤ 7.15, 91 ≤ a ≤ 97, the beryllium-zirconium alloy includes a face-centered cubic structure phase and a close-packed hexagonal structure phase, and the grain size ≤ 80 μm.
[0008] For the aspects and any possible implementation manners described above, a further implementation manner is provided. When 0 < d ≤ 2, 0 ≤ c ≤ 5.25, c < b ≤ 10.53, 87.72 ≤ a ≤ 92.86, the beryllium-zirconium alloy includes a face-centered cubic structure phase and a trigonal structure or a tetragonal structure phase, and the grain size ≤ 80 μm.
[0009] For the aspects and any possible implementation manners described above, a further implementation manner is provided. When 0 < d ≤ 2, 0 ≤ c ≤ 8.33, c < b ≤ 16.34, 81.7 ≤ a ≤ 89.48, the beryllium-zirconium alloy includes a trigonal structure phase and a hexagonal structure phase or a tetragonal structure phase, and the grain size ≤ 80 μm.
[0010] For the aspects and any possible implementation manners described above, a further implementation manner is provided. When 0 < d ≤ 2, 0 ≤ c ≤ 8.33, c < b ≤ 16.34, 65 ≤ a ≤ 83.34, the beryllium-zirconium alloy includes a trigonal structure phase, a hexagonal structure phase, a tetragonal structure phase and a face-centered cubic structure phase, and the grain size ≤ 80 μm.
[0011] For the aspects and any possible implementation manners described above, a further implementation manner is provided. When d = 1.55, c = 0.1, b = 7.5, a = 90.85, the atomic percentage expression of the beryllium-zirconium alloy is Be 90.85 Zr 7.5 M 0.1 X 1.55 , and the beryllium-zirconium alloy includes a face-centered cubic structure and a tetragonal structure phase, and the grain size ≤ 80 μm.
[0012] For the aspects and any possible implementation manners described above, a further implementation manner is provided. The melting point of the beryllium-zirconium alloy is greater than 1800 °C, and the neutron multiplication factor is close to 1.
[0013] According to the above aspects and any possible implementation, an implementation is further provided. When d=1.86, c=1.22, b=5.79, a=91.13, the atomic percentage expression of the beryllium zirconium alloy is Be 91.13 Zr 5.79 M 1.22 X 1.86 The alloy has a face-centered cubic structure and the grain size is ≤80um.
[0014] According to the above aspects and any possible implementation, an implementation is further provided. When d=1.61, c=0.08, b=8.28, a=90.03, the atomic percentage expression of the beryllium zirconium alloy is Be 90.03 Zr 8.28 M 0.08 X 1.61 , including face-centered cubic structure, tetragonal structure phase and trigonal structure phase, and the grain size is ≤80um.
[0015] The present invention also provides an application of the beryllium-zirconium alloy in a neutron breeder for a nuclear fusion reactor.
[0016] Beneficial Effects of the Invention
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The beryllium zirconium alloy with high temperature, high toughness and high neutron proliferation rate of the present invention has the atomic percentage expression of Be a (Zr b M c )X d , which has the following advantages:
[0019] 1. Beryllium-zirconium alloy has a large composition range and a wide range of preparation conditions.
[0020] 2. By adjusting the alloy composition, heat treatment, hot and cold processing technology, etc., controlling the phase composition and refining the grains, different high-temperature properties, mechanical properties and neutron multiplication properties can be obtained.
[0021] 3. The main elements of the high-temperature, high-toughness, and high-neutron proliferation rate beryllium-zirconium alloy material provided by the present invention are common metal raw materials and compounds, and can be prepared by different preparation methods, with the advantages of convenient preparation, simple process, and economy.
[0022] 4. The beryllium-zirconium alloy prepared by the present invention has excellent high-temperature performance, a melting point exceeding 1800°C, a neutron multiplication rate close to 1 (ie, less than or equal to 1), and excellent anti-irradiation swelling performance and mechanical properties.
[0023] 5. The beryllium-zirconium alloy provided by the present invention has excellent mechanical properties, high-temperature properties, excellent anti-irradiation swelling properties and neutron multiplication properties, and can be widely applied to the fields of neutron multiplication, plasma-facing materials and high-temperature materials. Description of the Drawings
[0024] Figure 1 It is the X-ray diffraction pattern of the beryllium-zirconium alloy of Example 1 of the present invention;
[0025] Figure 2 It is the microstructure diagram of the beryllium-zirconium alloy of Example 2 of the present invention. Detailed Embodiments
[0026] In order to better understand the technical solution of the present invention, the content of the present invention includes but is not limited to the specific embodiments hereinafter, and similar technologies and methods should be regarded as within the scope of protection of the present invention. To make the technical problems, technical solutions and advantages to be solved by the present invention clearer, the following will be described in detail with reference to the drawings and specific embodiments.
[0027] It should be clear that the embodiments described in the present invention are only a part of the embodiments of the present invention, rather than all the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments in the present invention without creative work shall fall within the scope of protection of the present invention.
[0028] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "the" and "said" used in the embodiments of the present invention and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.
[0029] The beryllium-zirconium alloy with high temperature, high toughness and high neutron multiplication rate of the present invention, the atomic percentage expression of the beryllium-zirconium alloy material composition is Be a (Zr b M c )X d , where M is one or more of Y, Ti, V, Mn, Fe, Mg, Cr, Co, W, Mo, Nb, Pb, Bi, Ta, Hf, Tl, Re, and X is one or more of O, C, N, P, S, Si, Al, Ca, Sc, Ni, Cu, U, 65 ≤ a ≤ 97, 3 ≤ b ≤ 35, 0 ≤ c ≤ 35, 0 < d ≤ 3, and a + b + c + d = 100.
[0030] The beryllium-zirconium alloy of the present invention uses neutron multiplication nuclides such as Be, Zr, etc., large-sized atomic refractory metal elements, low-activation elements such as Zr, W, Y, etc., and auxiliary phases such as Be 92.86 Y 7.14etc., to obtain a beryllium-zirconium alloy with characteristics of high temperature and high neutron multiplication rate, which is applied to neutron multiplier materials for fusion reactors, plasma-facing and other structural and functional materials under high temperature environments.
[0031] Furthermore, when 0 < d ≤ 2, 0 ≤ c ≤ 3.57, c < b ≤ 7.15, 91 ≤ a ≤ 97, the beryllium-zirconium alloy can be composed of face-centered cubic structure and hexagonal close-packed structure phases, with grain size ≤ 80um, having excellent toughness and high neutron multiplication rate.
[0032] Furthermore, when d = 1.86, c = 1.22, b = 5.79, a = 91.13, the atomic percentage expression of the beryllium-zirconium alloy is Be 91.13 Zr 5.79 M 1.22 X 1.86 , the alloy is of face-centered cubic structure, with grain size ≤ 80um, having high neutron multiplication rate, excellent toughness, high temperature performance, tritium retention and irradiation swelling resistance performance.
[0033] Furthermore, when 0 < d ≤ 2, 0 ≤ c ≤ 5.25, c < b ≤ 10.53, 87.72 ≤ a ≤ 92.86, the beryllium-zirconium alloy can be composed of face-centered cubic structure phase and trigonal structure phase or tetragonal structure phase, with grain size ≤ 80um, having excellent high temperature performance, tritium retention and irradiation swelling resistance performance.
[0034] Furthermore, when d = 1.55, c = 0.1, b = 7.5, a = 90.85, the atomic percentage expression of the beryllium-zirconium alloy is Be 90.85 Zr 7.5 M 0.1 X 1.55 , the alloy is composed of face-centered cubic structure and tetragonal structure phase, with grain size ≤ 80um, showing excellent toughness, processing performance, tritium retention and irradiation swelling resistance performance.
[0035] Furthermore, when d = 1.61, c = 0.08, b = 8.28, a = 90.03, the atomic percentage expression of the beryllium-zirconium alloy is Be 90.03 Zr 8.28 M 0.08 X 1.61 , the alloy is composed of face-centered cubic structure, tetragonal structure and trigonal structure phase, with grain size ≤ 80um, having good toughness, excellent high temperature performance, tritium retention and irradiation swelling resistance performance.
[0036] Further, when 0 < d ≤ 2, 0 ≤ c ≤ 8.33, c < b ≤ 16.34, 81.7 ≤ a ≤ 89.48, the beryllium-zirconium alloy can be composed of a trigonal structure and a hexagonal or tetragonal structure phase, with a grain size ≤ 80 μm, having a high neutron multiplication rate, excellent high-temperature properties, tritium retention properties, and irradiation swelling resistance properties.
[0037] Further, when 0 < d ≤ 2, 0 ≤ c ≤ 8.33, c < b ≤ 16.34, 65 ≤ a ≤ 83.34, the beryllium-zirconium alloy can be composed of a trigonal structure phase, a hexagonal structure phase, a tetragonal structure phase, and a face-centered cubic structure phase, with a grain size ≤ 80 μm, having excellent high-temperature properties, tritium retention, and irradiation swelling resistance properties.
[0038] Now, a method for preparing the beryllium-zirconium alloy of the present invention will be described.
[0039] The beryllium-zirconium alloy of the present invention and the preparation method for manufacturing neutron multiplier beryllium-zirconium alloy pellets using the beryllium-zirconium alloy are realized by hot isostatic pressing, plasma sintering, rotating electrode method, or powder metallurgy method.
[0040] The preparation of the beryllium-zirconium alloy by hot isostatic pressing includes the following steps:
[0041] S1.配料纯铍粉、钛粉及其它原料,按化学成分配比进行配料; S1. Mix pure beryllium powder, titanium powder, and other raw materials according to the chemical composition ratio.
[0042] S2.然后将配比的金属粉末拼混,然后灌装入包壳中进行高真空封焊,该金属包壳用于包裹金属粉末,再一起放到热等静压装置中采用热等静压方法压制成锭。此时的制造条件如下: S2. Then mix the proportioned metal powders, then fill them into a cladding and perform high-vacuum sealing. This metal cladding is used to wrap the metal powders, and then they are placed together in a hot isostatic pressing device and pressed into an ingot using the hot isostatic pressing method. The manufacturing conditions at this time are as follows:
[0043] 压强:60~1000MPa, Pressure: 60 - 1000 MPa,
[0044] 温度:300~1200℃, Temperature: 300 - 1200 °C,
[0045] 时间:0.5~6h。 Time: 0.5 - 6 h.
[0046] 等离子烧结法制备铍锆合金包括如下步骤: The preparation of the beryllium-zirconium alloy by plasma sintering includes the following steps:
[0047] S1.将纯铍粉、钛粉及其它原料,按化学成分配比进行配料; S1. Mix pure beryllium powder, titanium powder, and other raw materials according to the chemical composition ratio.
[0048] S2.然后将配比的金属粉末拼混,然后进行真空等离子体快速烧结,成型。此时的烧结条件描述如下: S2. Then mix the proportioned metal powders, and then perform vacuum plasma rapid sintering to form. The sintering conditions at this time are described as follows:
[0049] 真空度:1×10 Vacuum degree: 1×10 -1 pa~1×10 pa - 1×10 -10 Pa温度:300~1300℃ Pa Temperature: 300 - 1300 °C
[0050] 时间:0.5~6h Time: 0.5 - 6 h
[0051] Powder Metallurgy:
[0052] The method is used to manufacture neutron breeder beryllium zirconium alloy microspheres. First, the neutron multiplication material beryllium zirconium alloy prepared by the above method is used as the material, and then the material is loaded into a mold, crushed, and spheroidized to obtain the microspheres.
[0053] Rotating electrode method:
[0054] The neutron breeder beryllium zirconium alloy microspheres of the present invention are prepared by the rotating electrode method. First, the beryllium zirconium alloy prepared by the above method is made into a consumable electrode beryllium zirconium alloy rod. Specifically, the beryllium zirconium alloy can be machined into a specified electrode shape as a consumable electrode; then, the prepared consumable electrode is used to manufacture the neutron breeder beryllium zirconium alloy microspheres by the rotating electrode method. The manufacturing conditions at this time are not particularly limited, and the description of the preferred conditions is as follows:
[0055] Atmosphere gas pressure: 60MPa~1100MPa
[0056] Arc current: 100~1000A
[0057] Consumable electrode rotation speed: 5~1000m / s
[0058] [Example]
[0059] Example 1
[0060] A beryllium-zirconium alloy with high temperature, high toughness and high neutron proliferation rate, comprising: Be: 90.03 at.%, Zr: 8.28 at.%, O: 1.03 at.%, Fe: 0.08 at.%, and other elements including O, C, N, P, S, Si, Al, Ca, Sc, Ni, Cu, and U, which contains a total of 0.58 at.%, is prepared by hot isostatic pressing at a temperature of 1000°C and a time of 1.5 hours. Figure 1 As shown, the alloy consists of a face-centered cubic structure Be 92.86 Zr 7.14 Phase, tripartite structure Be 89.47 Zr 10.53 The alloy is composed of Be phase and close-packed hexagonal structure Be phase, with an average grain size of ≤80um, a neutron multiplication rate of up to 0.93, a nanoindentation hardness of 2.5GPa, excellent processing performance and fracture toughness. The properties are shown in Table 1, indicating that the alloy is particularly suitable for the field of neutron multiplication and high temperature.
[0061] Table 1
[0062]
[0063] The performance in Table 1 is described as follows:
[0064] Neutron multiplication performance refers to the neutron multiplication performance of the elements that constitute the alloy, and is evaluated by the neutron multiplication rate. Considering that beryllium is a naturally excellent neutron multiplication material, beryllium is used as a comparison material (the neutron multiplication rate is set to 1). The closer the performance of other materials is to 1, the better the neutron multiplication performance.
[0065] Tritium retention performance (a method of testing material performance, specifically injecting tritium into the material and then measuring the retention of tritium in the material). Since the purpose of fusion neutron breeder is to achieve self-sustaining tritium fuel, the retention of tritium in the material is also very important. A temperature decomposition gas analyzer (TDS) is used to measure tritium retention. That is, according to the degree of tritium retention, it can be excellent (very little retention), medium (partial retention), or poor (a lot of retention).
[0066] Anti-radiation swelling performance. Neutron irradiation materials will produce a large number of vacancies. These vacancies will further migrate and aggregate to form vacancy clusters such as holes, causing the volume swelling of the material. Under the conditions of high temperature 400℃ and helium injection of 3000appm, the irradiation swelling rate of metallic beryllium is >3%, endangering the safe operation of the reactor. It is assumed to have poor anti-swelling performance, and it is used as a comparison. The irradiation swelling rate is 1-3%, which is medium, and the irradiation swelling rate is less than 1%, which is excellent.
[0067] Other properties are well known in the industry and will not be specifically described. Due to differences in material composition, heat treatment process, hot and cold processing process, etc., the phase composition and grain size of the material are different, thereby regulating various properties of the material. For example, the alloy No. 1 in Table 1, which is composed of beryllium and titanium, can be obtained by proper annealing to obtain single-phase Be 92.31 Ti 7.69 The single phase is a tetragonal structure phase. Its neutron multiplication rate is measured to be 0.92, and its tritium retention performance is excellent. However, its fracture toughness and processing performance are particularly poor, and its later ball formation rate is particularly low, which seriously limits its application. The present invention uses beryllium and zirconium as the main elements, supplemented by other elements such as Y and Fe, and utilizes neutron multiplication nuclides such as Be, Zr, large-sized atomic refractory metal elements, low-activation elements such as Y, etc., and auxiliary phases such as Be 92.31 Fe 7.69 The grain size of the material is controlled by combining processes such as the above, thereby improving the neutron multiplication rate, toughness and high temperature performance of beryllium zirconium alloy.
[0068] Example 2
[0069] A high temperature, high toughness and high neutron proliferation rate beryllium zirconium alloy, the composition of which is: Be: 90.03at.%, Zr: 8.28at.%, O: 1.03at.%, Fe: 0.08at.%, other elements include O, C, N, P, S, Si, Al, Ca, Sc, Ni, Cu, U totaling 0.58at.%, vacuum plasma sintering at a temperature of 800°C for 1h, such as Figure 2 As shown, the atomic percentage expression of the alloy is Be 90.03 Zr 8.28 M 0.08 X 1.61 , the alloy consists of a face-centered cubic structure of Be 92.86 Zr 7.14 , tripartite structureBe 89.47 Zr 10.53 and close-packed hexagonal Be phase, with an average grain size of ≤80um, a neutron multiplication rate of up to 0.93, a nanoindentation hardness of 2.42GPa, excellent processing performance and fracture toughness. The performance data are shown in Table 1, indicating that the alloy can be used in the field of neutron multiplication and high temperature.
[0070] Example 3
[0071] A beryllium-zirconium alloy with high temperature, high toughness and high neutron proliferation rate, comprising: Be: 90.85 at.%, Zr: 7.5 at.%, O: 0.98 at.%, Fe: 0.1 at.%, and other elements including O, C, N, P, S, Si, Al, Ca, Sc, Ni, Cu, and U with a total content of 0.57 at.%, is sintered by hot isostatic pressing or plasma sintering, and then annealed at 1200°C for 2h. The alloy is composed of a face-centered cubic structure Be 92.86 Zr 7.14 and a very small amount of quartet Be 92.31 Fe 7.69 Phase composition, average grain size ≤80um, performance data are shown in Table 1, neutron multiplication rate>0.93, nanoindentation hardness 2.6GPa, high temperature, toughness and radiation swelling resistance are excellent, indicating that the alloy can be used in the field of neutron multiplication and high temperature.
[0072] Example 4
[0073] A high temperature, high toughness and high neutron proliferation rate beryllium zirconium alloy, the composition of which is: Be: 91.13at.%, Zr: 5.79at.%, Y: 1.22at.%, other elements include O, C, N, P, S, Si, Al, Ca, Sc, Ni, Cu, U total content 1.86at.%, the atomic percentage expression of the alloy is Be 91.13 Zr 5.79 Y 1.22 X 1.86 , prepared by hot isostatic pressing or plasma sintering, annealed at 1200℃ for 2h, the alloy is composed of face-centered cubic structure Be 92.86 Zr 7.14 and Be 92.86 Y 7.14Phase composition, average grain size ≤80um, melting point as high as 1800℃~1920℃, performance data as shown in Table 1, neutron multiplication rate 0.93, excellent processing performance and fracture toughness, indicating that the alloy can be used in the field of neutron multiplication, face-centered plasma materials and high temperature fields.
[0074] Example 5
[0075] A beryllium-zirconium alloy with high temperature, high toughness and high neutron multiplication rate, comprising: Be: 90.01 at.%, Zr: 5.22 at.%, Y: 2.1 at.%, V: 1.12 at.%, and other elements including O, C, N, P, S, Si, Al, Ca, Sc, Ni, Cu, and U with a total content of 1.62 at.%, is prepared by hot isostatic pressing to obtain a beryllium-zirconium multi-component alloy with an average grain size of ≤80 μm and a melting point of up to 1800° C. The performance data are shown in Table 1, the neutron multiplication rate is 0.92, and the toughness and radiation swelling resistance are excellent, indicating that the alloy is suitable for the neutron multiplication field and the high temperature field.
[0076] Example 6
[0077] A beryllium-zirconium alloy with high temperature, high toughness and high neutron multiplication rate, comprising: Be: 90.0 at.%, Zr: 6.2 at.%, Ti: 1.18 at.%, V: 1.1 at.%, and other elements including O, C, N, P, S, Si, Al, Ca, Sc, Ni, Cu, and U with a total content of 1.52 at.%. The alloy is prepared by a plasma sintering method to obtain a beryllium-zirconium multi-component alloy with an average grain size of ≤80 um. The performance data are shown in Table 1. The neutron multiplication rate is 0.92, and the resistance to radiation swelling and tritium retention are excellent, indicating that the alloy is suitable for the neutron multiplication field and the high temperature field.
[0078] The above description shows and describes several preferred embodiments of the present invention, but as mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not depart from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.
Claims
1. A beryllium-zirconium alloy, characterized in that: The atomic percentage expression of the beryllium-zirconium alloy material composition is Be a (Zr b M c )X d , where M is one or more of Y, Ti, V, Mn, Fe, Mg, Cr, Co, W, Mo, Nb, Pb, Bi, Ta, Hf, Tl, Re, and X is one or more of O, C, N, P, S, Si, Al, Ca, Sc, Ni, Cu, U, 65 ≤ a ≤ 97, 3 ≤ b ≤ 35, 0 < c ≤ 35, 0 < d ≤ 3, and a + b + c + d = 100.
2. The beryllium-zirconium alloy according to claim 1, characterized in that: When \(0 < d\leq2\), \(0 < c\leq3.57\), \(c < b\leq7.15\), \(91\leq a\leq97\), the beryllium-zirconium alloy includes a face-centered cubic structure phase and a close-packed hexagonal structure phase, and the grain size is \(\leq80\ \mu m\).
3. The beryllium-zirconium alloy according to claim 1, characterized in that: When \(0 < d\leq2\), \(0 < c\leq5.25\), \(c < b\leq10.53\), \(87.72\leq a\leq92.86\), the beryllium-zirconium alloy includes a face-centered cubic structure phase and a trigonal structure phase, and the grain size is \(\leq80\ \mu m\).
4. The beryllium-zirconium alloy according to claim 1, characterized in that: When \(0 < d\leq2\), \(0 < c\leq8.33\), \(c < b\leq16.34\), \(81.7\leq a\leq89.48\), the beryllium-zirconium alloy includes a trigonal structure phase and a hexagonal structure phase, and the grain size is \(\leq80\ \mu m\).
5. The beryllium-zirconium alloy according to claim 1, characterized in that: When \(0 < d\leq2\), \(0 < c\leq8.33\), \(c < b\leq16.34\), \(65\leq a\leq83.34\), the beryllium-zirconium alloy includes a trigonal structure phase, a hexagonal structure phase, a tetragonal structure phase and a face-centered cubic structure phase, and the grain size is \(\leq80\ \mu m\).
6. The beryllium-zirconium alloy according to claim 1, characterized in that: When d=1.55, c=0.1, b=7.5 and a=90.85, the atomic percentage expression of the beryllium-zirconium alloy is Be 90.85 Zr 7.5 M 0.1 X 1.55 The beryllium-zirconium alloy includes a face-centered cubic structure and a tetragonal structure phase, and the grain size is ≤80um.
7. The beryllium-zirconium alloy according to claim 1, characterized in that: When d=1.86, c=1.22, b=5.79, a=91.13, the atomic percentage expression of the beryllium zirconium alloy is Be 91.13 Zr 5.79 M 1.22 X 1.86 The alloy has a face-centered cubic structure and the grain size is ≤80um.
8. The beryllium-zirconium alloy according to claim 1, characterized in that: When d=1.61, c=0.08, b=8.28, a=90.03, the atomic percentage expression of the beryllium zirconium alloy is Be 90.03 Zr 8.28 M 0.08 X 1.61 , including face-centered cubic structure, tetragonal structure phase and trigonal structure phase, and the grain size is ≤80um.
9. Use of the beryllium-zirconium alloy according to any one of claims 1 - 8 in a neutron multiplier for a nuclear fusion reactor and in the high-temperature field.
Citation Information
Patent Citations
Material including beryllium intermetallic compound and having excellent high-temperature property applied to nuclear fusion reactor
US20050135960A1